Pengaruh Knowledge Management Pada E-Business (Studi Kasus Pada Driver Penyedia Jasa Transportasi Online) - Prakosa, Fajar (Sekolah Tinggi Ilmu Manajemen dan Ilmu Komputer ESQ (STIMIK ESQ), 2017)
The aim of this research paper is to evaluate the effect of knowledge management on the adoption of the e-business in driver online service transportation. Research methodology use quantitative approach with associative paradigm. Questionnaires were distributed to 200 driver Grab, Gojek, and Uber in Jakarta. Response rate of 89 percent. Data were analyzed by employing structural equation modeling with partial least square. The results showed that knowledge management processes such as knowledge acquisition, knowledge dissemination and knowledge application are significant in affecting provider of driver online service transportation decision to adopt e-business in their business.